Incremental Association Rule Mining using Incremental Discriminant Analysis - Piyush Kumar Dubey, Dr. Anil Rajput, Dr. Shailesh Jaloree (International Journal of Advanced Science and Technology, 2021)
This research paper discusses the development and implementation of Algorithm for computation of Incremental Association rules using Incremental Discriminant Analysis.This method has been used in different application fields for example it’s been used in market segmentation and market basket analysis. To authenticate the working of the algorithm we conducted experiments on benchmark dataset of Sixth Consolidated Bank. To improve target marketing, the Sixth Consolidated Bank want to identify the customers who are most likely to accept the loan offer. The data set includes a bunch of different predictors and the outcome variable is called personal loan. The predictor personal loan has a binary outcome in which the customer decides to accept or reject a loan.